踏跡尋中 - 蕭, 鳳霞 (The Chinese University of Hong Kong Press, 2025)
Tracing China explores nearly half a century of rural revolution and community reconstruction in South China, revealing China’s extensive influence and Hong Kong’s cross-border dynamics. Helen F. Siu, an anthropologist, examines the daily lives of ordinary people beyond cultural and physical landscapes, amidst political upheavals and dramatic changes as China modernizes. She highlights the concept of complicity, showing how villagers, urbanites, officials, entrepreneurs, and intellectuals carry historical burdens while questioning if they also become victims in the process.